Corporate social responsibility - Wickert, Christopher; Risi, David (Cambridge : Cambridge University Press, 2019)
This Element offers a thought-provoking and critical examination of corporate social responsibility (CSR). CSR has entered the boardroom and become a mainstream management concept for businesses to address their ethical, social and environmental responsibilities towards society. CSR does not come without contestation, and firms engage in CSR for different reasons and exhibit different patterns of CSR activities. These activities range from sincere action with substantial social or environmental improvements to symbolic impression management and the creation of a CSR-façade that is little more than empty words. This Element illuminates and scrutinizes contemporary approaches to CSR and offers a fresh perspective for scholars, managers and decision-makers interested in the societal role of business firms beyond maximizing profitability. Christopher Wickert and David Risi take a step back from how CSR is currently understood and practiced, and stimulate readers to reflect on how to move CSR forward towards a more inclusive concept.
Title from publisher's bibliographic system (viewed on 05 Jul 2019).
Keywords: Social responsibility of business